Clinical outcomes of levonorgestrel-releasing intrauterine device present during controlled ovarian stimulation in patients with early stage endometrioid adenocarcinoma and atypical endometrial hyperplasia after fertility-sparing treatments: 10-year experience in one tertiary hospital in China. (January 2023) - Yin, Jie; Li, Yan; Wang, Hanbi; Wang, Wei; Gu, Yu; Jin, Ying; Deng, Chengyan; Pan, Lingya
Abstract: Background: To evaluate the oncologic and pregnancy outcomes of patients with early stage endometrioid adenocarcinoma (EMC) and atypical endometrial hyperplasia (AEH) treated with controlled ovarian stimulation (COS) with or without levonorgestrel-releasing intrauterine device (LNG-IUD) after fertility-sparing treatment (FSTs). Methods: A total of 67 patients with EMC or AEH who achieved complete response after FSTs and underwent COS between January 2010 and December 2019 were retrospectively reviewed. Univariate and multivariate Cox regression analyses were used to evaluate the risk factors for recurrence after COS. Results: The average age was 32.9 ± 3.46 years. 23.9 % of these patients relapsed after COS during the follow-up period. The 2-year cumulative recurrence rate was 14.9 % (9.1 % and 20.6 % in the LNG-IUD and control groups, respectively). Compared with the control group, the recurrence rate was lower in patients with LNG-IUDs present during COS (12.1 % vs 35.5 %, p = 0.027). The clinical pregnancy (42.4 % vs 52.9 %, p = 0.392) and live birth (21.2 % vs 29.4 %, p = 0.444) rates were similar between the LNG-IUD and control groups. Age, body mass index (BMI), histology, FST type and time to complete response were not related to prognosis after COS. After adjusting for age and BMI in a multivariate Cox regression model, the use of LNG-IUD during COS was a favorable factor for better oncologic outcomes after COS (HR 0.263, 95 %CI 0.084–0.822, p = 0.022). Conclusions: Patients with early stage EMC and AEH treated with assisted reproductive technology after FSTs might benefit from LNG-IUDs present during COS.